2022
DOI: 10.1029/2021jc017718
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distributions of Riverine and Marine Dissolved Organic Carbon in the Western Arctic Ocean: Results From the 2018 Korean Expedition

Abstract: Seasonal primary production and river discharge increases in the Arctic Ocean exert a significant influence on the dissolved organic carbon (DOC) cycle. To improve our knowledge of the spatial heterogeneity of DOC source and concentration in the rapidly changing Arctic Ocean, we investigated the distributions of riverine and marine DOC in the western Arctic Ocean during the summer of 2018. Although the surface bulk DOC concentration indicated no clear distinction in its distribution between the Chukchi Borderl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 124 publications
0
4
0
Order By: Relevance
“…Given the ongoing climate change in the western Arctic Ocean, water mass structures are expected to be modified (Polyakov et al, 2017;Polyakov et al, 2020). Shoaling of the upper halocline layer, observed in our study region (Jung et al, 2021a;Jung et al, 2022), had the potential to supply humic-like FDOM to the euphotic zone. Thus, photodegradation of the humic-like FDOM, combined with the supply of inorganic nutrients to the surface layer, could enhance marine primary productivity in the western Arctic Ocean.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Given the ongoing climate change in the western Arctic Ocean, water mass structures are expected to be modified (Polyakov et al, 2017;Polyakov et al, 2020). Shoaling of the upper halocline layer, observed in our study region (Jung et al, 2021a;Jung et al, 2022), had the potential to supply humic-like FDOM to the euphotic zone. Thus, photodegradation of the humic-like FDOM, combined with the supply of inorganic nutrients to the surface layer, could enhance marine primary productivity in the western Arctic Ocean.…”
Section: Discussionmentioning
confidence: 82%
“…For the CBL and ESS, DOC river was set to be 175 mM C, corresponding to zerosalinity (100% river water) DOC value, obtained from the relationship between DOC and sea ice meltwater-corrected S in these regions (Figure S1). Details underlying the choice of DOC river in our study regions can be found in the publications by Jung et al (2021b) and Jung et al (2022).…”
Section: Estimation Of Riverine Dissolved Organic Carbonmentioning
confidence: 99%
“…A fraction of fresh DOC has biological origins from phytoplankton cells via physiological exudates, zooplankton grazing, and viral lysis . These processes release labile DOC that is bioavailable to heterotrophic microorganisms. , More refractory DOC is typically derived from terrestrial sources. , DOC is also released from sea-ice melt. , Concerning organic nitrogen, in studies around the Antarctic Peninsula, Dall′Osto et al , and Rinaldi et al suggested that DON can leak from melting sea ice and being incorporated into marine aerosols once transformed into methylamines, although the involved biological and chemical processes are poorly understood. However, we did not find any strong positive correlation between DOC or DON and SSA number concentration or aerosol size distribution (Table and Figures C and ), probably because the DOM components potentially active in changing air bubble properties and aerosol production were just a minor proportion of the total DOC and DON pools.…”
Section: Resultsmentioning
confidence: 99%
“… 80 , 81 More refractory DOC is typically derived from terrestrial sources. 82 , 83 DOC is also released from sea-ice melt. 47 , 84 Concerning organic nitrogen, in studies around the Antarctic Peninsula, Dall′Osto et al 54 , 85 and Rinaldi et al 86 suggested that DON can leak from melting sea ice and being incorporated into marine aerosols once transformed into methylamines, although the involved biological and chemical processes are poorly understood.…”
Section: Resultsmentioning
confidence: 99%